Wheat 14-3-3 Protein Conferring Growth Retardation in Arabidopsis - Jing LI; Su-sheng SONG; Yu-sheng ZHAO; Wei-wei GUO; Guang-hui GUO; Hui-ru PENG; Zhong-fu NI; Qi-xin SUN; Ying-yin YAO (Journal of Integrative Agriculture, 2013)
14-3-3 proteins belong to a family of phosphoserine/threonine-binding modules and participate in a wide array of signal transduction and regulatory events. Our previous study demonstrated that Ta14-3-3 was significantly down-regulated in leaf and root tissues of hybrid wheat at the tillering stage. In this paper, three homoeologous Ta14-3-3 genes were cloned from common wheat (Triticum aestivum L., 2n=6x=42, AABBDD) and mapped on chromosomes 2A, 2B, and 2D, respectively. Transgenic Arabidopsis plants ectopically overexpressing Ta14-3-3 displayed shorter primary roots, delayed flowering and retarded growth rates, indicating that Ta14-3-3 acted as a growth inhibitor in Arabidopsis. In wheat, Ta14-3-3 was down-regulated in roots and leaves of hybrids as compared to their parental lines. We proposed that Ta14-3-3 proteins might regulate growth vigor in hybrid wheat.